'How can more be done with less?': Investigating frugal innovation determinants using design thinking and interpretive structural modeling - Santos, M.; Ferreira, F.; Ferreira, N.; Carayannis, E. (IEEE Transactions on Engineering Management, 2024)
In the world today, innovation is an essential component of daily life. Companies deal with innovation on a regular basis to maximize their use of resources and form the foundations for competitive advantages over the competition. However, many firms currently face difficulties in terms of scarce resources and financial constraints, which has forced organizations to seek out new innovations that not only deliver good results but also require fewer natural and financial assets. Frugal innovation has thus been playing a significant role in companies' success and growing in importance as this concept and its various practical applications has become more fully defined. Frugal innovation's practical aspects are still insufficiently addressed by the literature, which shows a lack of clarity about possible determinants of this approach and the ways they are interconnected. This study develops a multicriteria model using two problem structuring methods—design thinking (DT) and interpretive structural modeling (ISM)—to clarify the issues that arise during frugal innovation. The results reflect the input of a group of experts linked to corporate innovation and/or small and medium-sized enterprises. The findings were subsequently analyzed and validated by a specialist who did not participate in the group work in order to make the analysis system more empirically robust. The proposed model provides a holistic view of determinants of frugal innovation, which can help companies understand and analyze these factors and engage in successful decision-making processes.